2010
DOI: 10.1053/j.gastro.2009.09.060
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Nuclear Receptor Signature With Epithelial Localization Patterns and Expression Modulation in Tumors

Abstract: We defined the intestinal nuclear hormone receptor map, which indicates that the localization pattern of a receptor in normal intestine predicts the modulation of its expression in tumors. Our results are useful to select those nuclear receptors that could be used eventually as early diagnostic markers or targeted for clinical intervention in intestinal polyposis and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 43 publications
4
72
1
Order By: Relevance
“…Several nuclear receptors that interact with PGC1α, such as PPAR-γ (Table S2) (33-35), farnesoid X receptors (FXRs) (36), retinoic acid receptors (RARs), and retinoid X receptors (RXRs) (37), modulate both differentiation and apoptotic pathways in the intestine with a potential pharmacological importance in colon cancer (38).…”
Section: Discussionmentioning
confidence: 99%
“…Several nuclear receptors that interact with PGC1α, such as PPAR-γ (Table S2) (33-35), farnesoid X receptors (FXRs) (36), retinoic acid receptors (RARs), and retinoid X receptors (RXRs) (37), modulate both differentiation and apoptotic pathways in the intestine with a potential pharmacological importance in colon cancer (38).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that VDR is expressed by normal and certain tumour colon epithelial cells (Sheinin et al 2000, González-Sancho et al 2006, Modica et al 2010 and is associated with a high degree of cell differentiation (Shabahang et al 1993, Zhao & Feldman 1993. VDR expression is enhanced in early stages of colorectal tumourigenesis (adenomas, polyps), whereas it decreases in advanced stages (Sheinin et al 2000, Larriba & Muñ oz 2005, Matusiak et al 2005.…”
Section: Angiogenesismentioning
confidence: 99%
“…The ability of FXR to reduce BA synthesis while inducing BA detoxification is of critical importance because high levels of circulating BA can increase hepatic and intestinal susceptibility to tumorigenesis (28 -31). Notably, the expression of FXR in the gut is restricted to the differentiated compartment of the intestinal epithelium (29,32), and its activation by BAs will result not only in BA detoxification but also in increased apoptosis and consequent removal of genetically modified cells (29,33). Indeed, the protective role of FXR against CRC susceptibility has been demonstrated by our group and others in Fxr knock-out mice, where the first hit for CRC development was made by inactivating Apc mutations (29,33).…”
mentioning
confidence: 89%